Military Spending and Stochastic Growth - Liutang Gong; Heng-fu Zou (Journal of Economic Dynamics and Control, 2003)
This study examines capital accumulation, military spending, arms accumulation, and output growth in a stochastic endogenous growth model. The analysis shows that higher (lower) growth in foreign military spending leads to faster (slower) economic growth in the home country if the home country¡¯s intertemporal substitution elasticity in consumption is smaller (larger); but more volatility in foreign military spending can lead to higher economic growth in the home country when its intertemporal substitution elasticity is large. In addition, shocks to output production may stimulate economic growth.